PENGARUH PENJUALAN KREDIT DAN PERPUTARAN PIUTANG TERHADAP LABA PADA CV. GEKA GEMILANG CIAMIS - Nursafaat, Firman; Saputra , Aldi Muhamad Hoerudin; Waldiana, Widi (Transpublika Publisher, 2022)
This study aims to determine the effect of credit sales and receivables turnover on CV. Geka Gemilang Ciamis profit. This study uses a descriptive method with the instrument used is secondary data and to analyze the data used product moment correlation test analysis tool and multiple linear regression test with a ratio measurement scale, as well as the coefficient of determination test. The statistical technique used to test the hypothesis is the correlation test or t-test and significance test for multiple correlation or f test. The results reveal that the credit sales has a positive and significant influence on profits at CV. Geka Gemilang, which is proven by 98% coefficient of determination. Moreover, receivables turnover has a positive and significant influence on profit at CV. Geka Gemilang which is proven by 98% coefficient of determination. Furthermore, credit sales and accounts receivable turnover also has a positive and significant influence on profits at CV. Geka Gemilang which is proven by 98% coefficient of determination.